The Cost of Grade Retention - Manacorda, Marco (The Review of Economics and Statistics, 2012)
This paper uses administrative longitudinal microdata on junior high school students in Uruguay to measure the effect of grade failure on students' subsequent school outcomes. Exploiting the discontinuity induced by a rule establishing automatic grade failure for pupils with more than three failed subjects, I show that grade failure leads to substantial dropout and lower educational attainment even four to five years after grade failure occurred.